A Conversation Analysis of Two-year-old Children’s Speech in Child-Adult Interactions - Titik Sudartinah (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Social interactions with adults around them are the main exposures to language that children receive, and these contribute significantly to their development. In response to this, this article examines the participation of two-year-old children in conversations with adults, aimed at describing the parties initiating conversation topics and identifying the structure of the conversations. The research used a qualitative method in the form of a case study, involving 5 children aged two years and their parents as participants. The data were collected through recorded natural conversations between children and parents. The results show that topics in child-adult interactions can be initiated by both parties. Furthermore, children have been able to build a complete conversational structure, consisting of opening, turn-taking, and closing. Several components of turn-taking, such as adjacency pairs and repairs are well performed. These findings suggest that, despite their limited language production, children at the age of two can actively participate in building and developing conversations with their interlocutors.